Resisting allegory : interpretive delirium in Spenser's Faerie Queene - Berger, Harry, Jr., 1924-2021 (Fordham University Press, 2020)
In Resisting Allegory, the leading Spenser critic of our time sums up a lifelong commitment to the theory and practice of textual interpretation. Central to this volume is an attention to the deployment of gender in conjunction with the Berger's notion of narrative complicity, all built on close attention to the text.